Long‐term safety of oral nucleos(t)ide analogs for patients with chronic hepatitis B: A cohort study of 53,500 subjects - Wong, Grace Lai‐Hung; Tse, Yee‐Kit; Wong, Vincent Wai‐Sun; Yip, Terry Cheuk‐Fung; Tsoi, Kelvin Kam‐Fai; Chan, Henry Lik‐Yuen (Hepatology (Baltimore, Md.), 2015)
Widespread and long‐term use of oral nucleos(t)ide analogs (NAs) to treat chronic hepatitis B (CHB) brings about safety data in a real‐life setting. We aimed to determine the risks of renal and bone side effects in patients receiving or who have received NAs as CHB treatment. A territory‐wide cohort study using the database from Hospital Authority, the major provider of medical services in Hong Kong, was conducted. We identified CHB patients by International Classification of Diseases, Ninth Revision, Clinical Modification diagnosis codes, diagnosed between 2000 and 2012. The primary events were renal (incident renal failure and renal replacement therapy [RRT]) and bone events (incident hip, vertebral, and all fractures). A 3‐year landmark analysis was used to evaluate the relative risk of primary outcome in patients with or without NA treatment. A total of 53,500 CHB patients (46,454 untreated and 7,046 treated), who were event free for 3 years, were included in the analysis. At a median follow‐up of 4.9 years, chronic renal failure, RRT, all fractures, hip fractures, and vertebral fractures occurred in 0.6%, 0.2%, 0.7%, 0.1%, and 0.1% of untreated subjects and 1.4%, 0.7%, 1.3%, 0.2%, and 0.2% of treated subjects. After propensity score weighting, NA therapy did not increase the risk of any of the events (hazard ratios [HRs] ranged from 0.79 to 1.31; P = 0.225‐0.887). Exposure to nucleotide analogues, compared with nucleoside analogs, increased the risk of hip fracture (HR = 5.69; 95% confidence interval: 1.98‐16.39; P = 0.001), but not other events (HR = 0.58‐1.44; P = 0.202‐0.823). Conclusions: NA treatment does not increase the risk of renal and bone events in general. Nucleotide analogs may increase the risk of hip fracture, but the overall event rate is low. (Hepatology 2015;62:684–693)